Maternal history of child maltreatment and maternal depression risk in the perinatal period: A longitudinal study. (January 2017) - Li, Yang; Long, Zhouting; Cao, Danfeng; Cao, Fenglin
Abstract: Existing research is limited, with only a few studies considering each single type and multiple types of child maltreatment (CM) as well as multiple assessments of maternal depression throughout the perinatal period. The purpose of the study was to assess each type and accumulative types of CM in relation to the risk of maternal depression throughout the perinatal period. In total, 276 pregnant women were recruited from the prenatal clinic at a general hospital in China. Maternal CM history and depression risk were assessed at late pregnancy, postpartum week 1, and postpartum week 4 using the Childhood Trauma Questionnaire (CTQ) and Edinburgh Postnatal Depression Scale (EPDS). The GEE showed that physical and emotional neglect and multiple types of CM were associated with higher overall depression risk across the perinatal period. The multinomial regression models showed physical neglect and multiple types of CM predicted higher risk of both antepartum and postpartum depression. Emotional and sexual abuse and emotional neglect predicted antepartum depression risk, while none of the three types of CM predicted postpartum depression risk. Physical abuse did not predict antepartum and postpartum depression risk. The findings suggest that maternal history of child physical and emotional neglect play significant roles in perinatal depression risk with physical neglect as the most important predictor. Routine screening for maternal CM history and depression risk in prenatal clinics is needed to aid in the early detection and treatment of depression.